2014
DOI: 10.1177/0269215514521044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi on balance and fall prevention in Parkinson’s disease: a randomized controlled trial

Abstract: Our findings suggested that Tai Chi exercise could improve the balance and decrease the fall risks in patients with Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 27 publications
2
131
0
1
Order By: Relevance
“…Many studies claim that taking regular exercises affects the improvement of motor and non-motor symptoms in these people. Indices of body posture control are important aspects affecting the independence maintenance and life quality among these patients who significantly look for improvable exercise interventions [5,28,29]. Different exercise interventions including aerobic exercises, hydrotherapy, balance exercises and walking could have significant treatment advantages with the increase of functional capacity among patients with Parkinson [7,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies claim that taking regular exercises affects the improvement of motor and non-motor symptoms in these people. Indices of body posture control are important aspects affecting the independence maintenance and life quality among these patients who significantly look for improvable exercise interventions [5,28,29]. Different exercise interventions including aerobic exercises, hydrotherapy, balance exercises and walking could have significant treatment advantages with the increase of functional capacity among patients with Parkinson [7,30].…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, Pilates is an exercise program which encourages the use of thinking for controlling muscles. It emphasizes the ability of muscles condition for balancing the body and supporting the improvement of vertebral column situation [29,41]. Considering the significant difference in the reduction of falling risk in Pilates group compared to the control one, it can be concluded that one period of exercise program based on Pi- [17,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies confirm the effectiveness of regular exercises on improving motor and non-motor symptoms in patients with PD. Postural control indices are significant and effective factors on maintaining independence and quality of life in these patients and significantly improve by training interventions [2, 16,33]. Different training interventions including aerobic exercises, hydrotherapy as well as balance and gait training cause significant therapeutic benefits by enhancing the functional capacity in these patients [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Binder et al, Campbell et al, King et al, and Gao et al in their studies mentioned that activities and exercises including balance training improve balance control [24][25][26][27].…”
Section: Acknowledgmentsmentioning
confidence: 99%